Complementary variable- and person-centered approaches to the dimensionality of burnout among fire station workers. Issue 4 (4th July 2022) - Sandrin, Emilie; Morin, Alexandre J. S.; Fernet, Claude; Gillet, Nicolas
ABSTRACT: This research relies on variable- and person-centered approaches to illustrate how each of these approaches may help to improve our understanding of the dimensionality of the burnout construct. Both studies (Study 1: N  = 247 administrative and technical employees; Study 2: N  = 654 firefighters), showed that employees' burnout ratings simultaneously reflected a global overarching construct co-existing with two specific dimensions (cynicism and emotional exhaustion), with a distinct factor reflecting reduced professional efficacy. In Study 1, perceived supervisor recognition and job satisfaction were associated with lower levels of global burnout levels. In Study 2, we examined the configurations, or profiles, taken by burnout dimensions (global burnout, specific cynicism, specific emotional exhaustion, and reduced professional efficacy), and documented associations between these profiles and four covariates (organizational, supervisor, and colleagues recognition as well as job satisfaction). Five profiles were identified using latent profile analyses: Very Low Burnout Risk, Mentally Distanced, Low Burnout Risk, High Burnout Risk, and Moderately High Burnout Risk . Employees' perceptions of supervisor and colleagues recognition were related to their likelihood of profile membership. Employees' job satisfaction levels also differed as a function of their profile.